2022
DOI: 10.3389/fphar.2022.909280
|View full text |Cite
|
Sign up to set email alerts
|

Nootkatone, a Sesquiterpene Ketone From Alpiniae oxyphyllae Fructus, Ameliorates Metabolic-Associated Fatty Liver by Regulating AMPK and MAPK Signaling

Abstract: Metabolic-associated fatty liver disease (MAFLD) is becoming more common due to lifestyle changes. A long-term high-fat and high-glucose diet induces glycolipid metabolism disorders in the liver, which results in the development of MAFLD. To date, there is no specific clinically useful therapeutics for this disease. Natural products or synthetic compounds were screened and investigated to find effective agents for treating MAFLD. In this study, nootkatone (Nok), a natural sesquiterpene ketone isolated from Alp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Similarly, significant reductions were observed in serum TC, TG, and GLU levels following AOP treatment ( Ghasemi and Nari, 2019 ). Nootkatone, mainly from Alpiniae Oxyphyllae Fructus , was shown to dramatically increase glucose consumption and decrease intracellular TG accumulation in L02 cells; this was supported by in vitro data in a study conducted by ( Yong et al, 2022 ). The incorporation of AOP into the diet at a concentration of 3 g/kg for laying hens was observed to have advantageous impacts on both the internal and external quality of eggs.…”
Section: Discussionmentioning
confidence: 56%
“…Similarly, significant reductions were observed in serum TC, TG, and GLU levels following AOP treatment ( Ghasemi and Nari, 2019 ). Nootkatone, mainly from Alpiniae Oxyphyllae Fructus , was shown to dramatically increase glucose consumption and decrease intracellular TG accumulation in L02 cells; this was supported by in vitro data in a study conducted by ( Yong et al, 2022 ). The incorporation of AOP into the diet at a concentration of 3 g/kg for laying hens was observed to have advantageous impacts on both the internal and external quality of eggs.…”
Section: Discussionmentioning
confidence: 56%
“…Up to now, there is no specific clinically useful therapy for MAFLD, thus some people try to screen and study natural products or synthetic compounds to find efficacious drugs for the treatment of MAFLD, such as the natural sesquiterpene ketone (Nok) ( 81 ), hydroxytyrosol (HXT), and vitamin E. Both HXT and vitamin E have good antioxidant properties ( 82 ), and oxidative stress is an influential factor that induces HSCs to activate and leads to liver fibrosis ( 83 ). HSCs can be activated by tumor growth factor TGF-β, leading to a significant increase in proliferation rate ( 84 ).…”
Section: Multi-drug Combination Therapiesmentioning
confidence: 99%
“…In vitro study also demonstrated that nootkatone increased glucose consumption and decreased triglyceride (TG) concentration. 164 In addition, a clinical study showed that the consumption of fresh grapefruit (active component being nootkatone) or grapefruit juice could produce significant reductions in body weight and the 2-h postglucose insulin level in metabolic syndrome patients, along with an increase in insulin resistance. 165 These findings suggested the potential of nootkatone to serve as a natural antiobesity product.…”
Section: Neuroprotective Effectmentioning
confidence: 99%